ANALISIS PENDAPATAN PEKERJA PARIWISATA DI KABUPATEN BADUNG, PROVINSI BALI - Widiana, I Nyoman Wahyu; Ni Putu Martini Dewi; Ni Putu Peri Eka Widiasih; Andi Ahmad Haidir (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
The existence of the hotel/villa industry, travel agents, and the restaurant/restaurant industry will be able to help people get jobs and increase their income in Bali, especially in Badung Regency. The formulation of the problem in this study is how the influence of education level, age, family size, and working hours partially and simultaneously affect the income of Bali Tourism workers. The sample of this study was tourism actors in Badung Regency in Bali Province, namely, hotels, restaurants/cafes, and travel agents using a purposive sampling method totaling 100 respondents. Data collection was conducted through observation, interviews, documentation studies, literature, and questionnaires. Data analysis techniques used multiple linear regression analysis, coefficient of determination, t-test and F-test. The results of the study showed that education level, age, family size and working hours had a significant simultaneous effect on the income of tourism workers in Badung Regency, Bali Province. Education level, age, family size and working hours had a significant partial effect on the income of tourism workers in Badung Regency, Bali Province. This research contributes to the understanding of how education level, age, family size and working hours had a significant simultaneous effect on the income of tourism workers in Badung Regency, Bali Province.